PERENCANAAN SISTEM PENYEGARAN UDARA UNTUK RUANG KELAS FAKULTAS TEKNIK UTA’45 JAKARTA - audri deacy cappenberg (JURNAL KAJIAN TEKNIK MESIN, 2018)
The comfort of classroom have a big impact to the studying activity or other activity inside the classroom, that is why   an air conditioning system should be planned while taking a lot of factors such as from inside and outside thr room into account, based on the calculation that has been done, it was found that the ventilated air that’s needed in the classroom is 4,1295 L/S, sensibel ventilation heat load for 25 persons of 2035 W, heat load generated for the north wall 80,64 W, east of 145,15 and west of 112,857 W. indoor heat load of 2649,87 W and outdoor heat load of1957,529 W. so the total capacity of the air conditioning  is 4607 W